In vitro screening of fungicides and tannins against fungal pathogens of jujube fruits - Hoque, MZ; Akanda, AM; Miah, MIH; Bhuiyan, MKA; Miah, MG; Begum, F (Progressive Agriculture, 2016)
The aim of this study to identify the effective fungicides for controlling major leaf and fruit diseases of Jujube caused by different fungal pathogens. An in vitro experiment was undertaken to screen ten fungicides and two Tannins against six important fungal pathogens of Jujube fruits which were Alternaria alternata, Colletotrichum gloeosporioides, Curvularia lunata, Lasiodiplodia theobromae, Fusarium semitectum and Pestalotiopsis palmarum. Fungicides were Conza 5 EC (Hexaconazole), Folicur 250 EC (Tebuconazole) and Potent 250 EC (Propiconazole), Bavistin DF (Carbendazim), Kasumin 2% liquid (Kasugamycin), Rovral 50 WP (Iprodine), Matco 72 WP (Mancozeb 64% + Metalaxyl 8%), Geneb 80 WP (Mancozeb), Emivit 50 WP (Copper oxychloride) and Evavit 80 WG (Sulphur 80 WG). And two tannins were Chestnut Tannin and Quabracho Tannin. Plain water was used as control. Poison food technique was followed to conduct the experiment. Both Tannins did not show satisfactory inhibition of mycelial growth of any of the six fungal pathogens. The effectiveness of fungicides varied greatly with fungal species. The most effective fungicides were Folicur 250 EC followed by Potent 250 EC, Rovral 50 WP, Conza 5 WP and Bavistin DF. Folicur 250 EC caused 89.52% inhibition of mycelium growth of A. alternata and 100% growth inhibition in other five fungi. In addition, Potent 250 EC inhibited growth of L. theobromae, C. lunata, F. semitectum and P. palmarum by 100% and that of C. gloeosporioides by 91.79%. Complete growth inhibition of F. semitectum and P. palmarum was achieved with Bavistin DF. Furthermore, Conza 5 EC caused 100% growth inhibition in C. lunata and more than 90% in L. theobromae and F. semitectum. Progressive Agriculture 27 (2): 154-161, 2016